The effect of COVID-19-related school closures on students' well-being: Evidence from Danish nationwide panel data - Simon Skovgaard Jensen; David Reimer (Elsevier, 2021)
We study the effect of the temporary closure of Danish schools as a result of the COVID-19 pandemic in spring 2020 on students' reported levels of well-being and test whether the effect varies among students of different socioeconomic status. To this end, we draw on panel data from the mandatory annual nationwide Danish Student Well-being Survey (DSWS) and exploit random variation in whether students answered the 2020 survey before or during the spring lockdown period. This enables us to compare reported levels of student well-being for selected measures - whether students "like school" and whether they "feel lonely" - among students in grades 6-9 to their responses from previous years. We use an event-study design with individual as well as year, month, and grade fixed effects. Our results indicate, firstly, that students' well-being with respect to liking school improved during the lockdown, even if students who answered during vs. before the lockdown were not on parallel trends in terms of previous levels of reported well-being. Secondly, school closures seemed to not affect students' reported levels of loneliness. Thirdly, the spring lockdown might have had a more positive impact among students of lower socioeconomic status.